Drug Rehabilitation Center based Survey on Drug Dependence in Dhaka City - Morshed Hasana; ASM Shahin (Update Dental College, 2014)
Background The study was conducted to know the socio-economic and demographic background of the drug addicts. The study also explored to identify the nature of drug used by the drug addicts and causes of drug addiction. Methods It was a descriptive cross sectional study conducted in a tertiary drug rehabilitation center in Dhaka city, Bangladesh. Purposive sampling strategy was followed and a closed ended questionnaire was utilized for face to face interview with the respondents. The data are analyzed through simple statistical calculation such as frequencies and percentages. Results A total 30 participants agreed to participate in the study. The highest concentration of drug addicts was between the age of 20 and 25 years (43.34%). However, near about half of the respondents (46.67%) took drug at the age of 16-20 years. It is quite alarming that 6.67% respondents took their first drug before the age of 10 and 16.67% took before the age of 15. Most of the addicts were students (40%) and over two thirds of the respondents (63.33%) had no knowledge on harmful impact on drug addictions. The most common type of drug used by the sample addicts were heroine (23.33) followed by Yaba (16.67%) and Phensedyl (16.67%). Familial problem was the main reason (40%) for getting involved with drug addiction followed by frustration of the respondents due to different reasons. Discussion The most important element of the drug demand reduction is the prevention which holds the key to success in the entire fight against drugs. Nationwide concerted action is needed to reduce the illicit demand for drugs. DOI: http://dx.doi.org/10.3329/updcj.v3i1.17982 Update Dent. Coll. j: 2013; 3 (1): 32-36